Keeper of Buryat Identity: The Phenomenon of Dashi Namdakov - R. E. Bolotov (Концепт: философия, религия, культура, 2023)
The article examines the work of the famous Russian sculptor and architect Dashi Namdakov. It is suggested that the origins of his talent lie in the depths of Buryat traditional art. The roots of Buryat art date back to the Paleolithic era, which is confirmed by the images of female figurines that were found by A. P. Okladnikov during the excavations of the prehistoric sites of the Baikal region. On the small sculptures made of mammoth bone, the lines of the face are finely worked out and the faces are framed in hair in the form of rays and snakes. Hats and clothes in these figurines are decorated with animal elements, which are considered to denote the native archaic culture which later appeared in a shamanic worldview. The basis of ancient art was syncretic and synthesized religious cult and myths. Later on ancient art, beliefs and ideas about the universe were incorporated in the cult images of the Buryat Mongols and today are communicated in a combination of archaic beliefs and esotery. This peculiarity of Buryat art leaves an original and unique imprint on modern art culture. Visitors of Dashi Namdakov's exhibitions get the feeling of an amazing connection between modernity and mythological antiquity. The article includes a short interview with the master jeweler Dashi Namdakov, in which he speaks about his work, about its origins and his future expectations.